VOLATILE CONSTITUENTS OF GINGER OIL PREPARED ACCORDING TO IRANIAN TRADITIONAL MEDICINE AND CONVENTIONAL METHOD: A COMPARATIVE STUDY - Shirooye, Pantea; Mokaberinejad, Roshanak; Ara, Leila; Hamzeloo-Moghadam, Maryam (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Herbal medicines formulated as oils were believed to possess more powerful effects than their original plants in IranianTraditional Medicine (ITM). One of the popular oils suggested for treatment of various indications was ginger oil. In the present study, tosuggest a more convenient method of oil preparation (compared to the traditional method), ginger oil has been prepared according to boththe traditional and conventional maceration methods and the volatile oil constituents have been compared.Material and Methods: Ginger oil was obtained in sesame oil according to both the traditional way and the conventional (maceration)methods. The volatile oil of dried ginger and both oils were obtained by hydro-distillation and analyzed by gas chromatography/massspectroscopy.Results: Fifty five, fifty nine and fifty one components consisting 94 %, 94 % and 98 % of the total compounds were identified in thevolatile oil of ginger, traditional and conventional oils, respectively.Conclusion: The most dominant compounds of the traditional and conventional oils were almost similar; however they were differentfrom ginger essential oil which has also been to possess limited amounts of anti-inflammatory components. It was concluded that gingeroil could be prepared through maceration method and used for indications mentioned in ITM.